2011
DOI: 10.1021/bi2008933
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial–Nuclear Communication by Prohibitin Shuttling under Oxidative Stress

Abstract: Mitochondrial-nuclear communication is critical to maintain mitochondrial activity under stress conditions. Adaptation of the mitochondria-nucleus network to changes in the intracellular oxidation and reduction milieu is critical for the survival of retinal and retinal pigment epithelial (RPE) cells, in relation to their high oxygen demand and rapid metabolism. However, the generation and transmittal of mitochondrial signal to the nucleus remains elusive. Previously, our in vivo study revealed that prohibitin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
81
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(91 citation statements)
references
References 49 publications
7
81
0
3
Order By: Relevance
“…The isolation of phosphoproteome or phosphopeptidome represents a potential challenge. Our data and other evidence suggest that phosphorylations are involved in apoptotic or protecting signaling under oxidative stress [Chung et al, 2009;Zhang et al, 2010;Arnouk et al, 2011;Lee et al, 2011;Sripathi et al, 2011].…”
Section: Phosphorylation Signaling In the Rpesupporting
confidence: 75%
See 1 more Smart Citation
“…The isolation of phosphoproteome or phosphopeptidome represents a potential challenge. Our data and other evidence suggest that phosphorylations are involved in apoptotic or protecting signaling under oxidative stress [Chung et al, 2009;Zhang et al, 2010;Arnouk et al, 2011;Lee et al, 2011;Sripathi et al, 2011].…”
Section: Phosphorylation Signaling In the Rpesupporting
confidence: 75%
“…We have focused on understanding the cell death mechanism of the retina and RPE under oxidative stress [Chung et al, 2009;Lee et al, 2010a;Lee et al, 2010b;Zhang et al, 2010;Lee et al, 2011;Arnouk et al, 2011;Sripathi et al, 2011]. Our studies demonstrated that oxidative stress may trigger induction of anti-apoptotic erythropoietin, JAK2, and BCL-xL, as well as pro-apoptotic caspases.…”
Section: Phosphorylation Signaling In the Rpementioning
confidence: 99%
“…92 Prohibitin (PHB) translocates from mitochondria to the nucleus under oxidative stress and seems have a dual function as an antiapoptotic molecule that maintains mitochondrial structure and as a transcriptional activator in the nucleus. 93 Prohibitin may also have roles in metabolic switching between glycolysis and fatty acid oxidation, roles as a nuclear transcriptional regulator in interaction with p53, E2F, and Rbn, and roles in regulation of cell cycle transit (see refs in 93). It is known to locate in the nuclear matrix in osteosarcoma MG-63 cancer cells 94 and in MCF7 cells we observed both PHB and PHB2 in the {m&n} protein set (Supporting Information Table 2).…”
Section: Sucrose Gradient Fractionation and Subcellular Protein Distrmentioning
confidence: 99%
“…Nuclearmitochondrial communication is necessary for the regulation of MtBIO [24]. Prohibitin (PHB), a conserved protein containing PHB domain, has been shown to regulate MtBIO [29], by regulating nuclear-mitochondrial communications [30]. It has been observed that prohibitin 1 (PHB-1) overexpression is related to chemoresistance in ovarian cancer [28].…”
Section: Chemoresistance Associated With Mtbiomentioning
confidence: 99%
“…MtBIO is the production of daughter mitochondria usually from previously existed one through a division process of called fission, subsequent growth, and maintenance by fusion and autophagy of mitochondria (mitophagy) [24]. Currently it has been observed that MtBIO is associated with cancer chemoresistance [25,26] through the modulation of associated proteins such as methylation-controlled J-protein (MCJ, also known as DNAJC15) [25,27], prohibitin 1 (PHB-1) [28][29][30], myeloid cell leukemia sequence 1 (MCL-1) [31,32] etc. in ovarian cancer.…”
Section: Introductionmentioning
confidence: 99%